2012
DOI: 10.1115/1.4007695
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Compact Torsional Spring for Series Elastic Actuators for Assistive Wearable Robots

Abstract: The introduction of intrinsic compliance in the actuation system of assistive robots improves safety and dynamical adaptability. Furthermore, in the case of wearable robots for gait assistance, the exploitation of conservative compliant elements as energy buffers can mimic the intrinsic dynamical properties of legs during locomotion. However, com-mercially available compliant components do not generally allow to meet the desired requirements in terms of admissible peak load, as typically required by gait assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 23 publications
(51 reference statements)
2
58
0
2
Order By: Relevance
“…This shape implies that the transfer of the torque between the outer and the inner parts of the spring occurs through flexible elements. The shape and dimensions of such flexible elements are defined through an iterative FEM simulation-based design and optimization process, as described in [22]. Considering the stiffness and the torque requirements in safe conditions (safety factor ≥ 2), the target storable elastic energy is 7.5 J, above the maximum value of the spring described in [22].…”
Section: Torsion Springmentioning
confidence: 99%
See 3 more Smart Citations
“…This shape implies that the transfer of the torque between the outer and the inner parts of the spring occurs through flexible elements. The shape and dimensions of such flexible elements are defined through an iterative FEM simulation-based design and optimization process, as described in [22]. Considering the stiffness and the torque requirements in safe conditions (safety factor ≥ 2), the target storable elastic energy is 7.5 J, above the maximum value of the spring described in [22].…”
Section: Torsion Springmentioning
confidence: 99%
“…Based on the authors' previous work [22], a compact, monolithic, torsion spring was designed for the rotary SEA. The desirable physical stiffness of SEAs for locomotion assistance, as retrieved from a literature analysis, may range from 100 to 300 N·m·rad −1 [20,21,[29][30][31].…”
Section: Torsion Springmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples include robotic hands, where the elastic elements are used to perform a stable grasp [1][2][3], flying robots, in order to estimate the pitch torques generated by wings during flapping [4] and robotic snakes, for estimating ground contact forces [5]. Furthermore elastic elements are key components of Series Elastic Actuators (SEAs) [6][7][8][9], Variable Stiffness Actuators (VSAs) [10][11][12][13][14][15][16][17][18] and, more generally, of Variable Impedance Actuators (VIAs) [19], where damping can also be adjusted by properly controlling the device. In this field, a seminal work is that of Fasse et al [20], where an electromagnetic variable impedance actuator is demonstrated, capable of exerting a torque much higher than that of the prototype described in this paper.…”
Section: Introductionmentioning
confidence: 99%